2019
DOI: 10.1016/j.ultrasmedbio.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Fiber Mapping of Rat Hearts, Using Apparent Backscatter, with Histologic Validation

Abstract: Myocardial fiber architecture is a physiologically important regulator of ejection fraction, strain, and pressure development. Apparent ultrasonic backscatter has been shown to be a useful method for recreating the myocardial fiber architecture in human-sized sheep hearts, due to the dependence of its amplitude on the relative orientation of a myofiber to the angle of ultrasonic insonification. Thus, the anisotropy of the backscatter signal is linked to, and provides information about, the fiber orientation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Prior to digestion, the most intense ultrasonic backscatter was visualized in areas of the myocardium where myofibers aligned perpendicular to the angle of insonification: backscatter intensity was comparatively reduced in areas of the myocardium with predominately parallel myofibers. This fiber‐alignment determinant of the anisotropy of ultrasonic backscatter has been previously validated (Milne et al., 2012, 2016, 2019). Throughout collagenase digestion, backscatter intensity increased disproportionally in areas where myofibers aligned parallel to the angle of insonification.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Prior to digestion, the most intense ultrasonic backscatter was visualized in areas of the myocardium where myofibers aligned perpendicular to the angle of insonification: backscatter intensity was comparatively reduced in areas of the myocardium with predominately parallel myofibers. This fiber‐alignment determinant of the anisotropy of ultrasonic backscatter has been previously validated (Milne et al., 2012, 2016, 2019). Throughout collagenase digestion, backscatter intensity increased disproportionally in areas where myofibers aligned parallel to the angle of insonification.…”
Section: Discussionmentioning
confidence: 84%
“…The highest backscatter intensity is generated where myofibers are aligned perpendicular to the angle of insonification and is lowest where myofibers are parallel. We, and others, have shown that anisotropy of ultrasonic backscatter relates directly to the alignment of myofibers, evidenced in both short and long‐axis ultrasonic images, of small and large mammals (Holland et al., 2005; Milne et al., 2012, 2016, 2019). Thus, myocardial backscatter is anisotropic, or variable, depending on the orientation of the ultrasound source and the myocardial myofiber (mesostructure) alignment.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In particular, we are aiming at clinical cine MRI acquisitions. The rule‐based assumption of cardiac fiber orientation could in future be personalized by diffusion tensor MRI 7 or quantified by echocardiography 8,9 . Since in case of using clinical data, there is no ground truth available to validate the method, we decided to first determine the accuracy of the reconstruction of active tension and its sensitivity to variation of model parameters using synthetic data.…”
Section: Introductionmentioning
confidence: 99%